The Effect of Using Word Detective Strategy on the Eleventh Grade Students’ Vocabulary Achievement at SMAN Pakusari in the 2016/2107 Academic Year - Shabrina Anindya Puteri; Bambang Suharjito; I Putu Sukmaantara (FKIP e-PROCEEDING, 2017)
Abstract:  The aim of this research was to investigate whether or not there was a significant effect of using word detective strategy on the eleventh grade students’ vocabulary achievement at SMAN Pakusari in the 2016/2017 academic year. Word detective strategy is one of the interesting strategies. It is a strategy in teaching vocabulary that makes the students become a detective to look for the meaning of the word by using context clues and word part clues. This research was conducted in SMAN Pakusari. The population of the research was the eleventh grade students of SMAN Pakusari in the 2016/2017 academic year. The researcher used cluster random sampling to choose the research respondents. The researcher applied Homogeneity test to know whether or not the condition of the population was homogeneous. Then, the result of the homogeneity test was analyzed by using ANOVA. Based on the homogeneity test, the population was homogeneous. Thus, the researcher used lottery to choose the experimental class and control class. The primary data were taken from the students’ vocabulary test and the supporting data were taken from the interview with the English teacher and the school documentation. The result of this research showed that there was a significant effect of using Word Detective Strategy on the eleventh grade students’ vocabulary achievement at SMAN Pakusari in the 2016/2017 academic year. Keywords: Word Detective, Teaching Vocabulary, Experimental Research.